2018
DOI: 10.11158/saa.23.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Paenibacillus lautus, an opportunistic bacterial pathogen, isolated from Ixodes granulatus Supino (Acari: Ixodidae) collected from a Müller’s giant Sunda rat (Sundamys muelleri)

Abstract: Wild rodents are carriers of ectoparasites such as ticks that are vectors of infectious diseases with human and veterinary significances. Due to their close association with human dwellings, synanthropic wild rodents may aid the spread and transmission of tick-borne pathogens. In light of this, an effort was initiated to study the cultivable bacteria within ticks collected from wild rodents trapped in Sungai Congkak Recreational Forest, Selangor. Ticks collected from four different rodent species; Sundamys mue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…Ampicillin, Penicillin and Cephalexin resistance of P. lautus is previously reported, which is in line with our finding (Bhullar et al, 2012, Celandroni et al, 2016, Loong et al, 2018. On the other hand, some findings are contradictory to our results, as some isolates of P. lautus were resistant against Clindamycin, Chloramphenicol and Erythromycin, which our isolate was sensitive to (Bhullar et al, 2012, Loong et al, 2018. In addition, resistance against Daptomycin, Telithromycin, and Piperacillin is also reported (Bhullar et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…Ampicillin, Penicillin and Cephalexin resistance of P. lautus is previously reported, which is in line with our finding (Bhullar et al, 2012, Celandroni et al, 2016, Loong et al, 2018. On the other hand, some findings are contradictory to our results, as some isolates of P. lautus were resistant against Clindamycin, Chloramphenicol and Erythromycin, which our isolate was sensitive to (Bhullar et al, 2012, Loong et al, 2018. In addition, resistance against Daptomycin, Telithromycin, and Piperacillin is also reported (Bhullar et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…To date, there is still lack of information on the behaviour of this rodent species, especially its ranging and nesting patterns, although numerous studies have reported their wide distribution across Malaysia and the Southeast Asian region (Lynam & Billick 1999;Esselstyn et al 2004;Paramasvaran et al 2005;Charles & Ang 2010). Loong et al (2018) has successfully cultured an opportunistic bacterial pathogen (Paenibacillus lautus) from ticks collected from this species. These opportunistic bacteria may be transmitted to humans and other host through tick bites and cause disease.…”
Section: Discussionmentioning
confidence: 99%
“…We employed a non-selective bacterial culture method in this study, previously shown to enable isolation of rare and pathogenic bacteria species from tick specimens such as Corynebacterium lactis (Lim et al, 2018) and P. lautus (Loong et al, 2018a). Even though no bacterial growth was observed for some tick specimens, we suggest that it was not due to the limitation of the agar culture media but the method employed for bacterial isolation (Stewart, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…All ticks were stored in 70% ethanol prior to transportation to the laboratory for analyses. In the laboratory, collected ticks were surface sterilized with 70% ethanol and rinsed thoroughly with nuclease-free water to remove all possible environmental contaminants (Loong et al, 2018a). Adult ticks were then sorted according to species, host, sex and blood meal status into pools of between 1 and Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation